Microrobots: Zwitterionic 3D‐Printed Non‐Immunogenic Stealth Microrobots (Adv. Mater. 42/2020). Issue 42 (20th October 2020) - Cabanach, Pol; Pena‐Francesch, Abdon; Sheehan, Devin; Bozuyuk, Ugur; Yasa, Oncay; Borros, Salvador; Sitti, Metin
Abstract : In article number 2003013, Salvador Borros, Metin Sitti, and co‐workers report stealth microrobots that can operate covertly under the immune system's radar. These stealth microrobots, fabricated from custom zwitterionic polymers for 3D microprinting, remain undetected by immune cells after exhaustive inspection, thus avoiding phagocytosis and immune clearance.